The Patterns of Socio-Perceptual Determination and Maternal Resilience - Anna A. Strelenko (National Research Mordova State University, 2023)
Introduction. The issue of socio-perceptual determination and resilience of the family is relevant to the implementation of state family policies in many countries. Family policy focuses on the family organization of orphans and children deprived of parental care, which contributes to the development of the institution of professional families. The problem is that the foster family system itself is very different from adoption and guardianship. And this due to the formation of the identity of the foster mother, who plays the main role in such a family. However, few studies have been conducted to determine the structure and content of the I-images of foster mothers. There is even less research on foster child images in foster mothers. Materials and Methods. The work was carried out with the participation of 295 women, from 19 to 71 years old, adoptive mothers (n = 86), biological mothers (n = 99), future mothers (no parenting experience) (n = 110). The study used the method "The structure of the image of a person (hierarchical)" (V. L. Sitnikov), and test "Resilience of an adult human" (A. V. Makhnach). Results. The functional relationship of socio-perceptual determination and resilience of mothers was defined. Mothers' self-perception identifies cognitive and regulatory components that influence coping and adaptation. In biological and future mothers, self-perception will include attitude. The perception of children by fostering mothers is that their resilience is linked to the regulatory, behavioral components of the social perception, neutrality or negative attitude. In childhood images, biological mothers relate their resilience to the cognitive, regulatory, behavioral components of social perception, positive or negative attitudes. In childhood images, expectant mothers relate their resilience to the cognitive, regulatory, behavioral components of social perception and negative attitudes. Discussion and Conclusion. The findings contribute to the development of perceptions of patterns of socio-perceptual determination and viability of different types of mothers.